2014
DOI: 10.1007/s13277-014-1714-6
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical/metabolic changes associated with hepatocellular carcinoma development in mice

Abstract: Hepatocellular carcinoma (HCC) is the third leading cause of cancer-related mortality after lung and stomach cancers. This work was undertaken to investigate some of the biochemical mediators/pathways associated with or implicated in the pathogenesis of HCC. Male albino mice were classified into two groups: normal control group and HCC group. Early stage HCC was induced by injection of diethylnitrosamine (DEN) i.p. 200 mg/kg as a single dose, and after 2 weeks, the mice were given i.p. injection of thioacetami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 37 publications
0
17
0
Order By: Relevance
“…CS presents either up-regulation or increased enzymatic activity in various cancer types such as ovarian and pancreatic cancer [67,68]. Noteworthy, CS enzyme activity has been reported to be increased in HCC [69]. More recently, RNAseq analysis-then verified in multiple microarray data sets-identified CS overexpression among unique 22-carbon-metabolism-gene signature of HCC [70].…”
Section: Citrate Synthasementioning
confidence: 99%
“…CS presents either up-regulation or increased enzymatic activity in various cancer types such as ovarian and pancreatic cancer [67,68]. Noteworthy, CS enzyme activity has been reported to be increased in HCC [69]. More recently, RNAseq analysis-then verified in multiple microarray data sets-identified CS overexpression among unique 22-carbon-metabolism-gene signature of HCC [70].…”
Section: Citrate Synthasementioning
confidence: 99%
“…Elevated G6PD activity, mRNA, and protein levels were also observed in rat preneoplastic nodules and HCC (75, 76) induced by the resistant-hepatocyte (R-H) protocol of carcinogenesis (77). Interestingly, a significant increase in serum G6PD activity has been recently seen in mice with HCC induced by DENA/thioacetamide (78). …”
Section: G6pd and Hccmentioning
confidence: 99%
“…Furthermore, in vitro using luciferase reporter assays, p53 expression was able to downregulate FGF21 promoter activity via the cis-acting sequence in the proximal promoter of FGF21. Consequently, when dysregulation of p53 protein expression occurs, a large number of FGF21 is activated in liver tissues [60]. Recently, a study showed that PPAR-a participates in hepatocarcinogenesis [56].…”
Section: Fgf21 In Hccmentioning
confidence: 99%